(untitled) (Discourse of Law and Administration, 2025)
The principle of financial independence is particularly linked to one of the budgetary principles, i.e. the principle of material unity. The article aims to describe the principles of financial independence and the principle of material unity in the financing of municipalities. To obtain this objectives, we focus on explaining the essence and goals of the principles of financial independence and the principles of material unity, as well as on exceptions to the principles of unity. The article bases on the dogmatic and legal method. The presented considerations lead to the conclusion that the introduction of many sources of exceptions to the principles of material unity results from additional regulatory arbitrariness, limiting decentralization and management independence.